A Study of Problems in Thai Speech of Chinese Students, Huachiew Chalermprakiet University - ธรรมวาจา วิไล (Academic and Research Journal of Liberal Arts (Online), 2018)
This research aims to Study the problems in Thai Speech of Chinese Students; Bachelor of Arts Program (B.A.) in Communicative Thai as a Second Language program of Huachiew Chalermprakiet University, and Study solutions to the problems in Thai Speech of Chinese Students; Bachelor of Arts Program (B.A.) in Communicative Thai as a Second Language program of Huachiew Chalermprakiet University. This research was a mixed method study. The sample selected with purposive sampling consisted of 58 Chinese students who registered for TC 3023 Thai Speech in order to collect information about the problem in Thai Speech as well as the suggested solutions. Seven teachers in Thai language and culture also provide information about the solution and how to improve the skills of Thai speech. The statistics used were the mean, standard deviation, frequency value and percentage. The results of the assessment of the ability of Thai Speech of Chinese students in 4 aspects were average between 3.04-3.83, at the moderate-high level. Ranking of the problem from the highest to the lowest level include content pr oblems, personality problems, language problems, and presentation problems. Teachers and students have a consistent consensus that the cause of the problem is a lack of knowledge, lack of language ability, un-reviewed, lack of preparation, anxiety and lack of experience. The proposed solution is to create a good Thai language base and how to use nonverbal language, practice, review and improve before presentation. It is recommended that the curriculum and universities should support students to participate in both internal and external competitions to enhance the experience and increase the efficiency of learning for foreign students.